Analytical assessment of tar generated during gasification of municipal solid waste : distribution of GC–MS detectable tar compounds, undetectable tar residues and inorganic impurities - Chan, Wei Ping (2021)
Tar, one of the most challenging impurities in the syngas generated from the gasification of municipal solid waste (MSW), can severely restrict its applicability in advanced utilization systems such as solid oxide fuel cells, gas engines and combined cycle gas turbines. Due to the complexity in sampling and analysis of tar, very limited studies have explored the development of comprehensive analytical procedure to provide insights into the distribution of GC–MS detectable tar compounds, GC–MS undetectable tar residues and inorganic impurities in the syngas from MSW gasification. In this study, Syngas generated from a downdraft fixed-bed gasifier (under different operating conditions) was sampled and analysed to understand the changes in the distributions of tar compounds and to verify the applicability of a sequential analytical procedure for syngas with different contents and distributions of tar and inorganic impurities. The procedure was developed to analyse and quantify the tar compounds and inorganic impurities in tar sampling solutions. The GC–MS analysis of three types of tar containing solutions (collected tar, gravimetric tar solution and evaporated condensate), gravimetric tar procedure (rotary evaporation and weighing), three separation/isolation methods (adsorption, dilution and decomposition) and quantification of inorganic compounds (cations and anions) were studied. With this sequential analytical procedure, enhanced detection and quantification (EDQ) of GC–MS detectable tar compounds at low concentration and correction on the GC–MS undetectable tar contents based on quantification of inorganic impurities were achieved. Distribution of tar and inorganic impurities was determined which revealed the impacts of operating conditions on syngas from MSW gasification.